Cáncer de mama y embarazo - Saade Aure, Miguel José (Gaceta Médica de Caracas, 2021)
El cáncer de mama asociado al embarazo es poco común; y se define como aquel diagnosticado durante el embarazo y hasta un año después del parto. La incidencia reportada es de 1/3 000 a 1/10 000 partos. Uno de los problemas del cáncer de mama asociado al embarazo es el diagnóstico tardío; debido a que los síntomas se atribuyen frecuentemente a los cambios fisiológicos de la gestación. Se revisan las opciones actuales de diagnóstico y tratamiento del cáncer de mama durante el embarazo y la lactancia. Breast cancer and pregnancy Breast cancer-associated with pregnancy is not very common, and it is defined as that type of cancer diagnosed during pregnancy and even until one year after childbirth. The report incidence is of 1/3 000 to 1/10 000 childbirths. One of the main problems of breast cancer-associated with pregnancy is the late diagnosis; because its symptoms are frequently attributed to the physiological changes that occurred during gestation. Present options of diagnosis and treatment of breast cancer during pregnancy and lactation are being reviewed nowadays.